SERVICE INNOVATION: LITERATURE REVIEW COMPARATIVE PRIVATE SECTOR AND PUBLIC SECTOR - Niluh Putu Dian Rosalina Handayani Narsa (Universitas Airlangga, 2018)
Public sector organizations have several unique characteristics that are not shared by private sector organizations. The differences in these characteristics eventually lead to differences in other, more specific matters. One of them is that it is traditionally seen that the development of innovation in the public sector is not too fast compared to innovation in the private sector, even though the public sector often faces more complex challenges so that in order to overcome it, innovative efforts are needed. This paper aims to determine the barriers to the emergence of innovation in the public sector through examining the differences in the characteristics of innovation in the public sector with the private sector, examining how public sector service innovations in several countries and in Indonesia. The study is complemented by reviewing empirical research that has been carried out by several researchers. Although this paper is descriptive and non-statistical, it is hoped that this paper can increase understanding of innovation in the public sector.